(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to enhance students’ branding design skills and awareness of Sustainable Development Goals (SDGs) through Canva-based training at SMAN 9 Denpasar. The program involved 36 twelfth-grade students and applied a participatory approach combining theoretical sessions, hands-on practice, and project-based mentoring. The results showed an improvement in students’ branding design skills, creativity, and soft skills such as communication and self-confidence. Students were able to develop simple branding concepts that integrate sustainability values. This program demonstrates that Canva-based training is an effective and accessible approach to fostering studentpreneur competencies in the digital creative economy.